Observer-based PD controller for balancing robot with uncertain model - Nguyen, Van Dong Hai; Nguyen, Minh Tam; Hoang, Ngoc Van; Nguyen, Thi Yen Tuyet; Mircea Ivanescu (Journal of Technical Education Science, 2017)
This research focuses on the observer-based controller of a balancing robot. Firstly, the dynamic model of the robot is inferred. The uncertainty of the model parameters is then introduced as constraints in state space. Practically, it is very difficult to measure state variables as velocity and acceleration. Moreover, system parameters are not always fixed in operating period. In order to avoid this difficulty, a nonlinear observer associated with the uncertain model system is used to estimate the state variables. A PD control algorithm is proposed in order to achieve the control performances. The exponential stabilities are ensured by Lyapunov techniques. Numerical simulations show the control performance successfully.